Aspect of Kombur Joke’s Focus on Literary Sociology - Harahap, Rosmawati (International Journal of Membrane Science and Technology, 2023)
Kombur jenaka Angkola-Mandailing which is a variant text version of the Batak comic text Angkola Mandailing. Data on the kombur jenaka of the Angkola-Mandailing community in rural areas was collected in 2006-2011. The humorous humor of Angkola-Mandailing with the text of the Angkola-Mandailing language is examined based on the topic of language form, the humorous comedy with the dimension of humorous stories in the literary aspects of Angkola-Mandailing. The Angkola-Mandailing kombur jenaka activity is studied by the elements of the kombur jenaka text form in literary sociology. Problem formulation: (1) what are the sociological aspects of the comedy metaphor prose text Angkola Mandailing; and (2) what types of metaphors are found in the Angkola-Mandailing joke texts? The aim of this research is to explain the sociological aspects of Angkola Mandailing’s kombur jenaka which is a metaphorical prose text; (2) want to explain the types of metaphors contained in the kombur jenaka text Angkola-Mandailing. The research methods used were observation, interviews and data dictation. The results of the research are descriptions of kombur jenaka text forms in the form of metaphors. In general, the Angkola-Mandailing kombur jenaka for the 2006-2011 period had the theme of the behavior of smart-stupid people.